2021
DOI: 10.1097/mao.0000000000003262
|View full text |Cite
|
Sign up to set email alerts
|

Novel Web-Based Music Re-Engineering Software for Enhancement of Music Enjoyment Among Cochlear Implantees

Abstract: Objectives: Cochlear implant (CI) listeners experience diminished music perception and enjoyment from a variety of patient-related and implant-related factors. We investigate the hypothesis that patient-directed music re-engineering may enhance music enjoyment with CI. Study Design: Prospective cohort study. Setting: Academic cochlear implant center. Subjects and Methods: A multidisciplinary team of neurotologists, audiologists, and a sound/audio engineer collaborated with a web developer to create a music re-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Given the amount of customization and complexity present in DAWs, they can be daunting applications for many users to engage with [4]. However, previous work has shown that even basic DAW controls can effectively be used to empower cochlear implant (CI) users to customize their music listening experience [7]. This is largely due to the reduced frequency resolution and speech-focused nature of CI processing.…”
Section: Introductionmentioning
confidence: 99%
“…Given the amount of customization and complexity present in DAWs, they can be daunting applications for many users to engage with [4]. However, previous work has shown that even basic DAW controls can effectively be used to empower cochlear implant (CI) users to customize their music listening experience [7]. This is largely due to the reduced frequency resolution and speech-focused nature of CI processing.…”
Section: Introductionmentioning
confidence: 99%
“…Like our colleagues, our group has been investigating music engineering since 2012, with presentations beginning in 2013, and the first publication in 2015 (1). These efforts have yielded five publications within our field culminating, most recently with the published work by Hwa et al (2–5). In the literature listed by the authors, our citations are similarly sparsely cited—supporting the authors' thesis of two disparate scientific communities that could benefit by building bridges.…”
mentioning
confidence: 99%